2015
DOI: 10.1007/s13361-015-1207-x
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Polyradical Protein Cations after an Electron Capture Event: Evidence for their Stable Distonic Structures in the Gas Phase

Abstract: Abstract. We report on the formation and Bcapture^of polyradical protein cations after an electron capture event. Performed in a unique electroncapture dissociation (ECD) instrument, these experiments can generate reduced forms of multiply protonated proteins by sequential charge reduction using electrons with~1 eV. The true structures of these possible polyradicals is considered: Do the introduced unpaired electrons recombine quickly to form a new two-electron bond, or do these unpaired electrons exist as rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…Multistep electron transfer to high charge states of proteins has been claimed to produce diradicals on the basis of their reaction with residual oxygen. 60 In contrast, the dissociations of doubly reduced heptanucleotide ions reported here indicated that no diradicals were formed.…”
Section: ■ Results and Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Multistep electron transfer to high charge states of proteins has been claimed to produce diradicals on the basis of their reaction with residual oxygen. 60 In contrast, the dissociations of doubly reduced heptanucleotide ions reported here indicated that no diradicals were formed.…”
Section: ■ Results and Discussioncontrasting
confidence: 54%
“…This may indicate that the transfer of the second electron in the 3 +• → 2 + reduction step resulted in the formation of a closed-shell dication and not a dication diradical. Multistep electron transfer to high charge states of proteins has been claimed to produce diradicals on the basis of their reaction with residual oxygen . In contrast, the dissociations of doubly reduced heptanucleotide ions reported here indicated that no diradicals were formed.…”
Section: Resultsmentioning
confidence: 52%
“…The Q-ToF MS is equipped with an ECD cell installed between lens electrode IQ2 and quadrupole q2 ( Figure 1) [28,29]. As such, this instrument can collect ECD spectra of precursor ions isolated by Q1 or it can collect conventional beam-type CID fragmentation spectra by accelerating Q1-isolated precursor ions through the ECD cell and into q2.…”
Section: Dms-ms Instrumentationmentioning
confidence: 99%
“…C: The acyl chain has two carbon-carbon double bonds at n-6 and n-9. [M- H+O 2 ] •+ is a product of a radical-ion, neutral reaction from the hydrogen lost precursor species, which is often observed in ExD (16).…”
Section: Modified Sms In Brain Smmentioning
confidence: 99%